(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Previous simulations associated with the heat and moisture transfer behaviors of clothing are mainly expressed with mathematical models, relevant computational algorithms and numerical solution methods and thus accessible to only a few professionals in the field. A software platform, called the S-smart system, was designed and developed as a friendly computer aided design tool with user friendly interfaces for users with little/limited background knowledge of technical information, complex physics, mathematics and computational techniques. The purpose of this study is to report a simulation test, using the S-smart system, for predicting the thermal functional performance of personal protective clothing. The results pertaining to skin temperature, core temperature and humidity in the clothing microclimate between the chest wall and underwear were compared with experimental data. Good agreement, both in terms of the trends of changes and overall mean values, is observed between the two. Furthermore, 2D and 3D visualizations of the S-smart system seemed to provide more evidence that explains the heat and moisture transfer mechanisms and predicts thermal functional performance of clothing.